(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2013)
Nowadays Geography is one of the most constructive sciences in the world. Due to the inner reflection it creates new categories such as geosystem. In this research the category of geosystem was analyzed and the integral definition of it was given. On this basis the role of geosystem was grounded in the sustainable development process of economical systems.